Pengaruh Kompensasi Rugi Fiskal, Profitabilitas, Proporsi Dewan Komisaris Independen, dan Ukuran Perusahaan Terhadap Tax Avoidance - dania ervina ervina; Trisninik Ratih Wulandari (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2019)
This study purposes to determine effect of fiscal loss compensation, profitability, proportion of independent commissioners and firm size to tax avoidance as measured using CETR. In this study, populations used mining companies listed on the Indonesia Stock Exchange during 2015-2017, the research samples obtained amounted to 51 companies during the period. The statistical tool used in this research is Eviews Vers 10 program in testing multiple linear regression. The results of this study found that in mining companies the proportion of independent commissioners has a significant positive effect on tax avoidance. Compensation of fiscal loss and firm size have a negative effect on tax avoidance, and profitability measured using ROA has no significant effect on tax avoidance.